Decoupling control of chassis integrated system for electric wheel vehicle. (May 2020) - Wu, Haixiao; Gao, Qi; Wang, Chunyan; Zhao, Wanzhong
In order to eliminate the mutual interferences among the differential assist steering system, the active suspension system and the electrical stability control, this paper proposes a sliding mode decoupling control strategy based on the inverse system method for the electric wheel vehicle. The dynamic model of the integrated chassis system is established, and the coupling relationship among the subsystems is analyzed by the correlation analysis. Based on the inverse system method, a compound pseudo linear system is constructed by an inverse system connected in series before the original chassis system, which is linearized and decoupled into three independent linear integral systems. In order to improve the robustness and anti-interference of the decoupled system, a pre-compensation controller based on the sliding mode control is designed for the pseudo linear system. The results of simulation and vehicle test show that the proposed decoupled controller has excellent decoupling performance, which can accomplish the single-channel control of the three decoupled subsystems, and eliminate their influences and interferences. Furthermore, it can effectively track the reference signal and reduce the impact of the external interference, which can obtain an excellent comprehensive performance of the chassis system.